Design and Development Augmented Reality Application to Introduce the Potential of Sudaji Village in Bali Using the Design Thinking Method - Wahyu, Kartika; Ashar, Muhammad; Kirana, Kartika Candra; Rahmadya, Budi (Journal of Disruptive Learning Innovation (JODLI), 2022)
Indonesia is a country that has diversity, both in terms of ethnicity, customs, religion, and language. One of them is the island of Bali, the island of Bali is one of the parameters of Indonesian tourism. Data on the high number of tourist visits to Bali before the pandemic increased. This is what affects the economy in Bali. However, due to the COVID-19 pandemic, tourists visiting Bali have decreased. In an effort to increase the economy due to the pandemic in the tourism sector, the Province of Bali continues to develop villages in Bali into tourist villages. One of them is Sudaji Village, Sudaji Village is included in the top 50 Indonesian tourist villages, the current digitization in the form of websites, YouTube, Instagram, Tiktok, Facebook which is used to provide information about the potential that exists in the village. However, the digitization is still not enough to encourage tourists to know about Sudaji Village, especially domestic tourists. This is evidenced by the results of interviews with five domestic tourists, stating that they have never heard of tourism in Sudaji Village, Bali. In the development of digital villages in Sudaji Village, namely using Augmented Reality (AR). Augmented Reality (AR) is a technology that has a lot of potential to be developed in various fields. This study uses the design thinking method with 5 stages, namely empathize to find out about the problems of potential users, define to define problems from the data that has been obtained, ideate, which is to create solutions or ideas based on existing problems, prototypes make products from the results of the previous stages, and the fifth stage, namely testing carried out by 5 potential users to get an SUS score of 82 which is included in the A value with excellent information.